2019
DOI: 10.1007/s00508-018-1434-9
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity in type 1 diabetes equal those of the general population

Abstract: Summary Background The obesity epidemic might affect patients with type 1 diabetes (T1DM), historically described as lean and insulin-sensitive subjects. Insulin resistance in T1DM might increase diabetic complications, especially cardiovascular disease. Therefore, the body mass index (BMI) in T1DM patients was analyzed in comparison to the general population. Furthermore, the impact of increased BMI on glycemic control and metabolic alterations was assessed. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 29 publications
4
32
0
1
Order By: Relevance
“…Overweight adults with T1D and inadequate glycaemic control comprise a population with an unmet medical need. Intensified insulin reduces the incidence and progression of long‐term diabetes‐related complications but is also associated with risks of hypoglycaemia and undesirable weight gain, which in turn are associated with increased cardiovascular risk 1,3 . Therefore, in addition to lowering blood glucose, reducing body weight and systolic blood pressure are of great importance in patients with higher BMI 1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overweight adults with T1D and inadequate glycaemic control comprise a population with an unmet medical need. Intensified insulin reduces the incidence and progression of long‐term diabetes‐related complications but is also associated with risks of hypoglycaemia and undesirable weight gain, which in turn are associated with increased cardiovascular risk 1,3 . Therefore, in addition to lowering blood glucose, reducing body weight and systolic blood pressure are of great importance in patients with higher BMI 1 …”
Section: Discussionmentioning
confidence: 99%
“…Up to 50% of adults living with type 1 diabetes (T1D) are overweight or obese 1,2 . Excess weight is associated with a high frequency of other cardiovascular risk factors 1,3 .…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies that reported the prevalence of overweight and obesity of T1D, which varies from 21-53.8% in different countries [24,[26][27][28]. The current study of children, adolescents and adults showed that the prevalence of being overweight or obesity was 16.9%.…”
Section: Comparison Of Demographic and Clinical Features Between Thismentioning
confidence: 49%
“…Tedavi alan hastaların büyük bir kısmının diyete uyum sürecini aksattıkları dönemlerde tekrarlayan medikal tedavi ihtiyaçları olduğu görülmüştür (15,16). Yapılan çalışmalarda obezite ile mikroalbuminüri arasında ilişki bulunurken mikroalbuminürisi olan 56 hastamızın sadece 7 si obezdi(p>0.05) (10,17). Hasta popülasyonumuzun genellikle sosyoekonomik ve sosyokültürel olarak dar gelirli ailelerden oluştuğunu varsayarsak bu oranın düşüklüğünü beslenme yetersizliği ile açıklayabiliriz.…”
Section: Discussionunclassified